Dendecultura no território de remanescentes de quilombos de jambuaçu no Baixo Tocantins - CASTRO, Auristela Correa (Universidade Federal do Pará, 2025)
The general objective of this research was to demonstrate how the expansion of dendeculture has affected the territories of traditional peoples and communities in Baixo Tocantins. As guiding axes in the clarification of these questions we use as specific objectives: to demonstrate the presence of dendeculture in communities of traditional people in Low Tocantins; to study the effects that the expansion of this monoculture of palm oil agribusiness has caused in the communities; demonstrate how these communities organize themselves in front of the advancement of this commodity in their territory; to analyze if the expansion of dendecultura, characterizes"land grab". In order to meet the feasibility of the research, the methodology used made a temporal cut in the implementation period of the PNPB until the date of the research, making an approach to the historical context and the process of genesis and the factors that allowed the implementation of the policy, taking into account the arena of public action, actors, values, algorithms, norms and images of that policy. As a result of the social sciences demand the confrontation of the real with research theory, (QUIVY, CAMPENHOUDT, 2005), the Quilombo de Jambuaçu Remnant Territory was chosen as the place of study, located in the "cradle of dendeculture", the Municipality of Moju in the Lower Tocantins Region, State of Pará. A description of this territory was made, as well as the designated communities as a locus of research. Non-directive exploratory interviews were conducted on an individual basis or in a family group, where ladies, misters, young people, as well as leaders or members of the community who experienced the process of formation of the territory and the arrival of oil palm (GIL, 2010; SEVERINO, 2007). In addition, the data were collected using data from the Global Positioning System (GPS). As for the bibliographic material that supported the research, it was searched on university websites, government websites, websites that discuss the subjects related to the research, as well as visits to public organizations that could provide important information to elucidate the subject studied. Theoretical basis on the peasantry and the labor relations that characterized it as such, was discussed on the peasantry in Brazil. The territory was also another concept sought. As PNPB's policy refers to a development model adopted by the Brazilian government for the Amazon were brought some approaches on development at a global level, at national level and as if that development in the Amazon, and finally was presented what it means " land grab ". Based on data analysis, it is concluded that dendeculture is present in communities of traditional people in the Lower Tocantins bringing numerous effects on the way of life of these peoples. It is also concluded that this expansion stems from a global context of capital advance in the world race for land to meet its expansion goals, which at its core is land grab.